Analysis Corrosion Rate Carbon Steel by Mg Anode and Na2Cr2O7 in Musi River Water Media - Komaini, M Ali; Ariyanto, Eko; Sri Yusmartini, Eka; Oktaviansyah, Ikbal (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to analyze and optimize the effect of Mg anode and sodium dichromate sacrificial protection on the corrosion rate of carbon steel in Musi River water media. The research involved carbon steel pipes (½ inch, 1 cm length) with an ID of 18.20 mm and OD of 18.80 mm. Four variables were tested: A (no corrosion prevention), B (Na2Cr2O7), C (Mg anode), and D (Na2Cr2O7 with Mg anode), each immersed in 150 ml of Musi River water for periods of 20, 30, 40, 50, and 60 days. Results showed the highest pH drop in variation A, where the initial pH of 6.87 decreased to 4.13 after 60 days. Variation A also showed the greatest increase in Fe concentration, rising from 1.47 mg/L to 4.89 mg/L, and turbidity from 80.8 NTU to 88.3 NTU after 60 days. Corrosion rate analysis indicated that carbon steel without corrosion prevention had the highest corrosion rate, reaching 0.0000025746 mpy after 60 days. In comparison, carbon steel with Na2Cr2O7 and Mg anode protection exhibited significantly lower corrosion rates. These findings highlight carbon steel pipes without corrosion protection experience higher degradation in Musi River water, while sodium dichromate and Mg anode treatments effectively reduce corrosion.